Activating KIR Copy Number Variation Is Associated with Granzyme B Release by NK Cells during Primary Simian Immunodeficiency Virus Infection in Rhesus Monkeys - Hellmann, Ina (American Society for Microbiology, 2012)
Here we show that the number of activating killer cell immunoglobulin-like receptor (KIR) copies in rhesus monkeys is associated with the extent of release of cytotoxic granules by cytolytic NK cells during primary simian immunodeficiency virus SIVmac251 infection. These findings suggest that NK cells expressing high levels of activating KIRs efficiently kill SIVmac251-infected cells, and this efficient killing contributes to the NK cell-mediated control of replication of this virus during early infection.